Metformin: Is it Still the First Line in Type 2 Diabetes Management Algorithm? - Grammatiki, Maria; Sagar, Rebecca; Ajjan, Ramzi A. (Current Pharmaceutical Design, 2021)
Type 2 diabetes mellitus (T2DM) has an ever-growing prevalence worldwide, affecting 1 in 11 adults. It continues to significantly impact patients in terms of morbidity and mortality, in addition to impairing quality of life while adding to the spiralling healthcare costs. Metformin was first used over half a century ago, and for the past two decades, it has been considered first-line oral therapy to treat patients with T2DM, in whom lifestyle measures failed to improve glycaemic control. Early landmark studies supported a glycaemic benefit with metformin use with a relatively safe adverse effect profile, particularly with avoidance of hypoglycaemia. Moreover, studies have indicated other potential beneficial role for metformin on organs typically affected by diabetes complications. However, more recently, with the discovery of newer hypoglycaemic agents and the wealth of data provided by large-scale cardiovascular safety studies, algorithms for the treatment of patients with T2DM have become increasingly complex. Indeed, recent guidelines challenge current thinking and advocate the use of agents other than metformin as first-line agents in those with higher cardiovascular risk, potentially unseating metformin from its long-held throne. This narrative review aims to summarize the background and origins of metformin, assess its role in the current management of patients with T2DM, highlighting the clinical efficacy and safety profile of this agent. Also, the position of metformin in the clinical algorithms is discussed in light of the most recent evidence in the field, helping with an ever-increasing shift towards individualized patient care to maximize benefits and minimize risks.
Keywords: T2DM